Good Governance Memediasi Hubungan Pengelolaan Keuangan Daerah dan Sistem Pengendalian Intern Pemerintah terhadap Kinerja Instansi Pemerintah (Studi Empiris OPD Kabupaten Solok) - Nur Azlina (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2019)
This study aims to examine and analyze the relationship of regional financial management and internal control systems of government with the performance of government agencies mediated by good governance. The dependent variable used is the performance of government agencies, the independent variable used is regional financial management and government internal control systems and one mediating variable in the form of good governance. The population in this study is the Solok District Organization of 26 OPDs. The sampling technique used in this study is saturated sampling with 76 respondents. This study uses primary data. Data collection techniques based on survey method by providing a set of questionnaires to respondents.Path analyisis is used to test the hyphotesis.